Factors Impacting Research Productivity at Higher Educational Institutions in Kazakhstan - Yassinova, Kuralay (Nazarbayev University Graduate School of Education, 2019)
In some universities low level faculty research productivity has become a critical issue that negatively affects their obtention of high results in university rankings, which in turn, is instrumental in improving the economic growth of the country. In this regard, one of the prioritized goals set by Kazakhstan is to increase the quality and frequency of faculty research productivity to better interact and contribute to the globalized knowledge-based economy. Moreover, Kazakhstani policy makers and leaders in education are taking measures to tackle the current problem related to low level faculty research productivity. Despite measures taken to improve research productivity, publication rates remain low. This is a function of various factors that may affect the interest and motivation of faculty to pursue research. The issue that this research project addresses is that not all faculty members are involved in research, and those who only conduct research unwillingly or under the professional pressure to do so. The purpose of this study is to explore the factors that impact faculty research productivity and define the motivational influences that encourage faculty to conduct research. This study employed an in-depth interview based qualitative approach. To gather the data, maximal variation sampling within a purposeful sampling format was used, and fifteen participants were selected from within two groups: junior faculty and senior faculty who were examined to determine the salient characteristics and traits they possessed, and which affected their motivation to conduct research. The results of this study have provided information on the factors that impact research productivity and the kinds of motivational influences that stimulate faculty to pursue research. This study provides insight on the measures that could be taken by policy makers and university administration to prevent the negative factors and support the positive ones that motivate faculty to conduct research.
Keywords: Factors Impacting Research Productivity; Impact; Higher Educational Institutions; HEI; FIRP; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education